Monitoring of Energy Rates of Domestic PV Systems to Evaluate the Influence of Occupants’ Behavior on Environmental and Economic Benefits - Marilena De Simone; Antonio Bilotta (Buildings)
The use of photovoltaic systems in residential buildings represents a solution for reducing CO2 emissions and users’ bill costs. To fully experience these advantages, however, correct use of the solar technology is necessary. Many researchers have already directed their studies towards human interaction with traditional energy systems, highlighting how the presence of users at home increases energy consumption and costs. This aspect is still less explored in the case of buildings that integrate smart and innovative technical solutions for energy production. This study aims to highlight how monitoring, data collection, and analysis can be critical to obtain effective operation of PV systems, considering technical features and user behavior in parallel. To quantify these aspects, three domestic users were analyzed by collecting data for one year. The parameter “Social Investment Index SII” was introduced to estimate the economic and environmental profitability of the investment. The available funding at the end of the life of the systems was strongly affected by the occupancy and behavioral efficiency of the user, with a potential increase of up to 55%, or a decrease higher than 70%. The SII varied from 23.6 to 18.4 kg of CO2 saved/(k€ ∙ MWh) in the case of ineffective user behavior.